Implementasi Algoritma Adaptive Huffman Code Dalam Kompresi File Teks Terenkripsi Algoritma Loki97 - Rahmad Syahputra (Journal of Computing and Informatics Research, 2021)
Data security and confidentiality is one of the most important aspects in today's information systems. Due to the rapid development of science and technology that allows the emergence of new techniques, which are misused by certain parties that threaten the security of the information system. The fall of information into the hands of other parties can cause harm to the owner of the information. Therefore we need a way that can provide security for the data, one of which is using cryptographic techniques. Cryptography technique is a science or art in fulfilling security aspects in communicating by changing the content of information into incomprehensible information. One of the algorithms that can be used is the Loki97 algorithm, which is a cryptographic algorithm that uses the Feistel network system. The process carried out in this study is to first encrypt the text file using the Loki97 algorithm, then the results of the encrypted file will be compressed using the Adaptive Huffman Code algorithm, resulting in an encrypted and compressed file.